Drumband Extracurricular Implementation at SMP Negeri 1 Batang Anai - Febrionaldo; Hadi, Harisnal (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study intends to describe how the process of implementing extracurricular drumband at SMP Negeri 1 Batang Anai. This type of research is qualitative using descriptive methods. The instruments in this study are the researchers themselves and assisted by other instruments such as stationery, cameras and voice recorders. This research uses data collection techniques, namely observation, interviews, documentation and literature studies. The steps to analyze data in this study are collecting data, identifying and concluding. The results obtained in the study were to recruit Drumband members and the trainer did not make a selection first. As a result of gaps or imbalances in instrument selection, students prefer percussion instruments compared to melodic instruments. In the process of extracurricular implementation, this drumband activity at SMPN 1 Batang Anai is carried out once a week and the activities of each meeting are the same, it's just the difference in the material of the song you want to learn. The schedule in this extracurricular activity is carried out on Monday, namely in order to evaluate the flag ceremony activities in the morning. However, there is an additional jawdal if there is a training activity if it accompanies the parade and accompanies the teacher's day ceremony.